Analysis Of Current Ratio And Debt To Equity On Return On Equity (Case Study of a Pulp and Paper Sub-Sector Company for the 2017-2022 Period) - Pratama, Muhammad Jordy; Yusnita, Rita Tri; Lestari, Suci Putri (Universitas Dehasen Bengkulu, 2024)
This research aims to analyze and determine the partial influence of Current Ratio (CR) on Return On Equity (ROE). To analyze and find out whether there is a partial influence of the Debt to Equity Ratio (DER) on Return On Equity (ROE). To analyze and determine the influence of the Current Ratio (CR) and Debt to Equity Ratio (DER) simultaneously on Return On Equity (ROE). The population used in this research is pulp and paper sub-sector companies listed on the Indonesian Stock Exchange (BEI) for the 2017-2022 period. The sample selection for this research was determined using the purposive sampling method, where the researcher selected the sample based on the assessment of sample members' criteria which were adjusted to certain considerations. Based on these criteria, there are 7 companies in the pulp and paper sub-sector that are the research samples. The type of data used is secondary data originating from publications on the official websites of related companies and the Indonesian Stock Exchange (BEI) in the form of annual financial reports. For data collection, documentation techniques were used. The data analysis technique used is panel data regression with the help of SPSS 23. Based on the research results, it is concluded that the Current Ratio (CR) and Debt to Equity Ratio (DER) simultaneously have a significant effect on Return On Equity (ROE). Partially, Current Ratio (CR) has no significant effect on Return On Equity (ROE). Meanwhile, Debt to Equity Ratio (DER) partially has no significant effect on Return On Equity (ROE).